Dictionary of the North-west Semitic inscriptions - Hoftijzer, J. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2003)
The North-West Semitic epigraphic contributes considerably to our understanding of the Old Testament and of the Ugaritic texts and to our knowledge of the North-West Semitic languages as such. This dictionary is concerned with the North-West Semitic material found in inscriptions, papyri and ostraca in Phoenician, Punic, Hebrew, various forms of Aramaic, Ammonite, Edomite, the language of Deir Alla et cetera. The material covers the period from circa 1000 B.C. to circa 300 A.D. Besides translations, the entries include discussions and full references to scholarly literature. The book is a translated, updated and considerably augmented edition of Jean andamp; Hoftijzer, Dictionnaire des inscriptions sémitiques de l'ouest . The additions concern newly found texts as well as references to new scholarly literature. The book is an indispensable tool for research in North-West Semitic epigraphy, on the Old Testament and on Ugaritic texts, and for Semitic linguistics. Please note that this version is an unrevised reprint of the original version published in 1995.